Validasi dan Penetapan Kadar Rhodamin B pada Lipstik yang Beredar di Sekitar Universitas Jember dengan Metode KLT-Densitometri (Validation TLC-densitometry method for determination of Rhodamine B in Lipstick at Jember University Area) - Risa Wahyu Ananda; Nia Kristiningrum; Yuni Retnaningtyas (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Rhodamine B is one of the synthetic dyes that forbidden in cosmetics. The study was conducted to validate TLC-densitometry method for determination Rhodamin B in lipstick at Jember University area. Samples was taken by purposive sampling method. The analyte were dissolved with ethanol 70% and cromatographed on silica Gel GF 254 TLC plate using etil asetat : metanol : amoniak in the ratio (15:3:3) (v/v/v). Then, validation and determination sample can be done using TLC-densitometry with maximum wavelength 554 nm. Method was found linear over the concentration range of 6 – 32 ng with correlation coefficient of 0,9965. Spesificity showed calculation of purity and identity more than 0.99. The limits of detection and quantitation limits obtained 0.558 and 1.86 ng/spot. The precision test which includes precision repeatability and intermediate precision, amounting to RSD 6.57% and test accuracy , resulting % recovery and RSD value of 97.74 % ± 2.54% . Based on these results lipstick sample purposively sampled none containing rhodamine B and safe consumer use. Keywords: TLC - densitometry , lipstick , rhodamine B , the validation method of analysis